Penerapan Model Adi (Argument Driven Inquiry) Berbasis Argumentasi Toulmin Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik SMA - Firdaus Kirani Annisanastiti; Suliyanah (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
Efforts that can be made to facilitate the improvement of students' critical thinking skills are to apply the ADI (Argument Driven Inquiry) learning model. It is a learning model that gives students opportunity to learn in reflective scientific inquiry so they can develop argumentation skills and critical thinking. The purpose of this study was to obtain data on (1) implementation of ADI model on sound wave material, (2) improvement students' critical thinking skills after applying ADI model based on Toulmin's argumentation. The type of research is true experiments with pre-test-post-test control group research design. Data collection was carried out using observation, tests and questionnaires. The results showed that learning physics using ADI model could be carried out very well with percentage score of 94,23%. The results of pre-test and post-test data analysis shows that the increase of critical thinking skills of experimental class students is in medium category and control class is in low category. The results of student response questionnaire data analysis showed that stages of ADI model were implemented well in class with percentage score of 84,16%. This shows that ADI model can be used to improve students' critical thinking skills.